Patch-recorded single-channel currents of the purified and reconstituted Torpedo acetylcholine receptor. - Tank, D W (1983)
Small unilamellar vesicles containing purified and reconstituted nicotinic acetylcholine receptors from Torpedo electroplax have been fused by a simple freeze-thaw procedure to form large liposomes. Giga-seal patch-recording techniques were used to form isolated patches of liposome-membrane and to measure single-channel properties of the reconstituted receptor-ion channel complex. The observed properties are quantitatively similar to those reported for vertebrate muscle nicotinic acetylcholine receptor species recorded in situ. The results demonstrate that the pentameric complex consisting of the alpha 2 beta gamma delta subunits is fully functional. The methods used in these experiments should be useful in studying the effects of chemical alterations on the properties of acetylcholine receptor channels as well as other types of purified and reconstituted ion channels.